Development of a ready-to-drink (RTD) Batuan (Garcinia binucao (Blco.) Choisy) juice - Villasis, Jasper C. (College of Home Economics, University of the Philippines Diliman, 2019)
This study aimed to develop a ready-to-drink (RTD) batuan juice. Specifically, the study: (a) evaluated the effects of formulation variables on response variables sweetness, sourness, flavor, overall acceptability, total soluble solids (TSS), % titratable acidity (%TA), and pH of RTD batuan juice using a three-component D-optimal mixture design; (b) optimized the formulation of the RTD batuan juice using three-component D-optimal mixture design; and (c) determined the proximate composition, microbiological safety, and antioxidant activity of RTD batuan juice. Results revealed that all response variable models were significant (p < 0.05). Linear relationships were found for sweetness, sourness, TSS, % TA, and pH while modified cubic models were obtained for flavor and overall acceptability. Verification runs show that the models are accurate in predicting the models. Optimum RTD batuan juice formulation comprised of 76.4-81.6 g water, 13.1-10.0 g batuan puree, and 8.4- 9.4 g white sugar. The obtained optimum formulation has acceptable sweetness, sourness, flavor and overall acceptability (target = 6), a TSS of 9.53, %TA of 2.64%, and pH of 2.81. Proximate analyses showed that the optimum RTD batuan juice formulation contains 7.18g/100mL total available carbohydrates which is accounted to the added sugar and a significant amount of crude fiber at 1.34 g/100mL which is greater than dietary fiber-fortified guava juices at 0.25g/100mL. The optimum RTD batuan juice formulation contains appreciable amount antioxidants, which is higher than commercially available fruit juices. Microbiological analyses also showed that the product was safe for consumption.